Effects of the Chemical Compositions of Salars de Uyuni and Atacama Brines on Lithium Concentration during Evaporation. Issue 2 (April 2014) - Ogawa, Yasumasa; Koibuchi, Hiroshi; Suto, Koichi; Inoue, Chihiro
Abstract: During Li recovery from salar brines, Li concentration is typically increased to about 60, 000 mg L −1 by evaporation. We investigated the concentration changes of Li, Na, K, Mg, Cl, SO4, and B during evaporation of both natural Uyuni and artificial Atacama brines. The Uyuni brine exhibited a maximum Li concentration of 6810 mg L −1 at 31 days of evaporation, at which point the majority of the Na and K in the brine was removed. The Li concentration decreased with further evaporation due to precipitation as Li2 SO4, such that the level at the 56 day mark was approximately 4130 mg L −1 . In contrast, the artificial Atacama brine showed no pronounced Li precipitation, even after 54 days, at which point the Li concentration was 21, 800 mg L −1 . The initial concentrations of Na and K in the Atacama brine were higher than those in the Uyuni brine, and the Atacama solution still retained K after 54 days of evaporation. The order of precipitation of cation species during the evaporation of both brines was: Na, followed by K, Mg, and Li. Thus, Li precipitation in the Atacama brine might be prevented due to the more favored precipitations of Na and K, such that significant Li removal did not occur in this brine. Abstract : The order in which cations precipitated from the Uyuni brines concentrated by evaporation was: Na, followed by K, then Mg and Li. If the evaporation had continued, further Li concentration would not necessarily be expected.